The impact of umbilical cord care education given to Primiparous mothers on cord separation time: A randomized controlled study - Merter, Ozlem Selime; Karakul, Atiye; Karaarslan, Duygu (Elsevier Science Inc, 2023)
Purpose: This study aims to determine the impact of umbilical cord care education given to primiparous mothers on cord separation time. Design and methods: This randomized controlled trial was conducted according to the Consolidated Standards of Reporting Trials (CONSORT) guidelines. The mothers constituting the research sample were divided into two groups, the control group and the education group, and cord care and cord separation times were measured. Results: The mean age of the mothers was 28.72 +/- 4.86 years (min. 20 years, max. 40 years). There was no difference in age, gestational week of the baby, birth weight of the baby, gender of the baby and mode of delivery of the mother between the mothers in the control and education groups. While the cord separation time was 10.97 +/- 0.320 days in the babies in the control group, it was 6.60 +/- 0.177 days in the babies in the education group. A statistically significant difference was found between the duration of cord separation of the babies in the control and education groups. Conclusions: This study showed that giving umbilical cord care education to primiparous mothers reduces umbilical cord separation time. Practice implications: It is recommended that pediatric nurses provide education on umbilical cord care and the goals and methods of application of care practices, especially to primiparous mothers. Clinical registration: This study was registered at the U.S. National Library of Medicine Clinical Trials (code:
Keywords: Umbilical cord care; Primiparous mothers; Cord separation time; Education